If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X2-14X-1=9
We move all terms to the left:
X2-14X-1-(9)=0
We add all the numbers together, and all the variables
X^2-14X-10=0
a = 1; b = -14; c = -10;
Δ = b2-4ac
Δ = -142-4·1·(-10)
Δ = 236
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{236}=\sqrt{4*59}=\sqrt{4}*\sqrt{59}=2\sqrt{59}$$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-14)-2\sqrt{59}}{2*1}=\frac{14-2\sqrt{59}}{2} $$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-14)+2\sqrt{59}}{2*1}=\frac{14+2\sqrt{59}}{2} $
| 6l+45=8l+15 | | x/0.3=100 | | 26-6n=2 | | 4v+6=3v+4v | | X=3x+4=3-9 | | 4x+x=335 | | 3/2x=12/40 | | 12-x=(2x+22) | | X=-2,y=-5 | | 13-4x+7+5x=80 | | 2x+38+x+20=3x | | 4x+15+6x+5=2x+45 | | 4-2(x+7)=3(x | | 6(2-x)=2(x+12)^0-11x | | 8x-4=6x+9 | | 30+3x-15-2x=105 | | 17/12=x | | 4(2x-1)=6x+9 | | 1÷4d=3 | | 14x-6=2x+8 | | 2x-23+x-3=8 | | 1/2x+30=1/3x | | 2x+7=-4x+16 | | 2/7w-6=^2 | | .5(26+24x)=2(6.5x-9) | | 5(x–2)=8+3x | | 7x+2=3x–5 | | 11+2x+3=5x+2+x | | X^3+5x^2+2x=-10 | | 3-4x=10x | | 12=14b−3+3 | | 3x=−4 |